Community Knowledge, Beliefs, and Actions Regarding the use of Antibiotics in Sibuntuon Village, Uluan Toba District - Rosnike Merly Panjaitan; Hilda Hilda; Masrah Masrah; Mawar Sihombing (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Antibiotic use is relatively high in Indonesia, which will enhance the occurrence of resistance. Community understanding of receiving antibiotics is critical for treatment success and preventing resistance occurrences. The goal of this study was to describe the level of community understanding regarding the use of antibiotics in Sibuntuon Village, Uluan District, Toba Regency. This is a descriptive survey method, using 96 samples taken by the technique Simple Random Sampling in April-May 2021. The results showed that 24 respondents (25%) had good knowledge in the good category, 47 respondents (48.96%) in the fairly good category, 22 respondents (22.92%) in the bad category and 3 respondents (3.12%) in the bad category. Confidence of good respondents by 17 respondents (17.71%), in the quite good category 76 respondents (79.17%), while the category is not good by 3 respondents (3.12%) and 0 respondents (0%) in the category is not good. The actions of respondents who had a good level were 23 respondents (23.96%), in the quite good category there were 33 respondents (34.38%), while the unfavorable category was 37 respondents (38.54%), and the category was not good as many as 3 respondents (3.12%). The conclusion of this study is that the knowledge, attitude beliefs, and actions of using antibiotics in the community in Sibuntuon Village, Uluan District, Toba Regency are quite good. and there is an influence between the level of knowledge, attitudes, and actions towards antibiotic use with a significant value of 0,000. The findings of this study can inform that education regarding the use of antibiotics, both directly education and through various educational media, must continue to be carried out in the community. Keyword: Actions, Antibiotics, Attitudes, Knowledge